Fertility-related interplay between fungal guilds underlies plant richness–productivity relationships in natural grasslands - Chen, Wenqing; Wang, Jianyu; Meng, Zexin; Xu, Ran; Chen, Jun; Zhang, Yingjun; Hu, Tianming (The New phytologist, 2020)
• The plant richness–productivity relationship is a central subject in ecology, yet the mechanisms behind this pattern remain debated. Soil fungi are closely associated with the dynamics of plant communities, however empirical evidence on how fungal communities integrate into the richness–productivity relationships of natural environments is lacking. • We used Illumina high-throughput sequencing to identify rhizosphere fungal communities across a natural plant richness gradient at two sites with different fertility conditions, and related the subsequent information to plant richness and productivity to elucidate the role of fungal guilds in integrating the linkages of both plant components. • Saprotrophs, mycorrhizal fungi and potential plant pathogens interacted differently between the sites, with saprotrophic and mycorrhizal fungal abundances being positively correlated at the high-nutrient site and abundances of mycorrhizal fungi and potential plant pathogens being negatively correlated at the low-nutrient site. The synergistic associations between these fungal guilds with plant richness and productivity operated in concert to promote positive richness–productivity relationships. • Our findings provide empirical evidence for the importance of soil fungal guilds in integrating the linkages of plant richness and productivity, and suggest that future work incorporating soil fungal communities into richness–productivity relationships would advance our mechanistic understanding of their linkages.